Perbandingan Kinerja Keuangan Perusahaan Telekomunikasi Di Indonesia Sebelum Dan Setelah Pandemi Covid-19 - Muhammad Hafizh; Hastuti (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This study aims to determine the differences in the financial performance of telecommunications companies before the Covid-19 pandemic and after the Covid-19 pandemic. Financial performance is measured using several ratios, namely liquidity ratios, solvency ratios, and profitability ratios. The type of research conducted is descriptive quantitative research. The population in this study were all telecommunication companies listed on the IDX, namely 6 companies, the sample was collected from 4 company financial statements in 2019 and 2020 using the convenience sampling method. The analysis was carried out by comparing the liquidity ratios, solvency ratios, and profitability ratios of the sample companies before the Covid-19 pandemic and after the Covid-19 pandemic took place. The results of this study indicate that the telecommunications companies sampled experienced a decrease in almost all ratios analyzed during the Covid-19 pandemic, but did not experience a change in their financial performance status.